(untitled) (Perner’s Contacts, 2018)
The aim of the study was to map spin-off companies in conditions of the University of Zilina in Zilina, namely on the Faculty of Operation and Economics of Transport and Communications and the Faculty of Management and Informatics. A detailed analysis of entrepreneurial activities of pedagogues, researchers, scientific workers and PhD. students was conducted considering their traffic orientation. The main task was to identify transport companies and then assess their cooperation with the university and decide if it is a spin-off company based on the chosen definition.